The Planned Expansion of the “30+ Union” and the Allocation of Seats in the European Parliament - Barcz, Jan (Roczniki Nauk Społecznych, 2024)
The subject of the article concerns the formula for the allocation of seats in the European Parliament given the planned EU enlargement. The course of work on this issue is discussed in the light of the provisions of the Treaty of Nice and the Treaty of Lisbon. The importance of this problem was pointed out, especially regarding the new decision-making formula in the EU Council by qualified majority. However, it is very difficult to agree on a permanent system that guarantees compliance with the principle of degressive proportionality in the allocation of EP seats. Rather, it should be assumed that the distribution of seats in the European Parliament during the finalization of the planned EU enlargement will be, as it has been so far, primarily the result of a political contract between the member states.